Association between exposure to cadmium and risk of all-cause and cause-specific mortality in the general US adults: A prospective cohort study. (November 2022) - Li, Zhi; Fan, Yun; Tao, Chengzhe; Yan, Wenkai; Huang, Yuna; Qian, Hong; Xu, Qiaoqiao; Wan, Tingya; Chen, Yiyuan; Qin, Yufeng; Lu, Chuncheng
Abstract: Background: Cadmium has been suggested to accumulate in the body over a lifetime, posing a great threat to human health. So far, few studies have studied the association between cadmium exposure and long-term health outcomes in adults. Objectives: To investigate the risk of mortality with blood cadmium level in adults (participants of NHANES, 1999–2014). Methods: We evaluated the associations between cadmium and risk of mortality. Data on mortality and cadmium exposure were collected in NHANES database including 39, 865 participants. Multivariate Cox regression models were established for calculating hazard ratios (HRs) and 95%CI between cadmium exposure and all-cause and specific-cause mortality outcomes. Results: Totally, 39, 865 individuals with 19, 260 males (48.3%) and 20, 605 females (51.7%) were included in the study. During a total of 341, 017 person-years of follow-up 5, 094 deaths were documented, including 1, 067 cardiovascular disease (CVD) and 890 cancers. Compared with the lowest quantile of cadmium exposure level group, the adjusted HRs in the highest quantile cadmium exposure level group were 1.73 (95%CI: 1.52–1.97) for all-cause mortality, 1.72 (95%CI: 1.28–2.30) for CVD mortality and 1.87 (95%CI: 1.49–2.36) for cancer mortality, respectively ( P for trend: <0.001). Additionally, significant interactions with smoking status in the stratified analyses of all-cause mortality and cancer mortality, age in the stratified analyses of cancer mortality were found ( P for interaction: 0.002, <0.001 and 0.012). Conclusions: In this nationwide representative sample of the population, we found that higher blood cadmium concentration was associated with increased risks of all-cause and specific-cause mortality. These data further evidence the link between mortality and cadmium concentration. It is of great importance for both policy makers and the public to minimize cadmium exposure, and to reduce long-term adverse health effects. Graphical abstract: Image 1 Highlights: We explored independent effects of cadmium on all-cause and specific cause mortality. Cadmium was positively related to all-cause, CVD and cancer mortality. Smoking modified upwards the association between Cd and all-cause, cancer mortality. Age modified upwards the association between Cd and cancer mortality. The U-shaped dose-response curves between cadmium and mortality were observed.